Management of urolithiasis in pregnancy. (16th March 2023) - Chan, Kimberley; Shakir, Taner; El-Taji, Omar; Patel, Amit; Bycroft, John; Lim, Chou Phay; Vasdev, Nikhil
Abstract: Urolithiasis is the most common cause of nonobstetric abdominal pain, resulting in 1.7 admissions per 1000 deliveries. Urolithiasis most commonly occurs in the second and third trimesters, with an incidence between 1:125 and 1:2000. Acute urinary system obstructions are challenging to manage in obstetric patients because they contribute to physiological and anatomical changes that result in pathological outcomes. The restricted use of computed tomography in diagnosing and managing urolithiasis is particularly challenging. In addition, a prompt diagnosis is required because the presence of renal calculi during pregnancy increases the risk of fulminating sepsis and preterm delivery. Affected pregnancies are conservatively managed; however, 1 in 4 requires surgical intervention. Indications for surgical interventions are complex and range from nephrostomy insertion to empirical stent placement or ureteroscopy. Therefore, a multidisciplinary approach is required to optimize patient care. The diagnosis and management of urolithiasis in pregnancy are complex. We reviewed the role, safety, advantages and disadvantages of diagnostic tests and treatment used to manage acute urinary obstructions in pregnancy.